2019
DOI: 10.1007/s00159-019-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Small Solar System Bodies as granular media

Abstract: Small solar system bodies as granular media 3

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 323 publications
(395 reference statements)
0
24
0
1
Order By: Relevance
“…Beyond the terrestrial gravity that we experience every day-and, in particular, when gravity is weaker-exploration and sampling missions must carefully consider their destination when designing instruments. This holds true for destinations like our Moon (Nash et al 1993) or other planets, where gravity is at least comparable to that of Earth, but also for the extreme case of asteroids, where gravity can be 4-5 orders of magnitude weaker (Hestroffer et al 2019). As examples of the latter microgravity regime, indeed the surfaces of both (101955) Bennu (Barnouin et al 2019) and (162173) Ryugu (Watanabe et al 2019) have been shown to be composed of loosely bound rubble.…”
Section: Introductionmentioning
confidence: 88%
“…Beyond the terrestrial gravity that we experience every day-and, in particular, when gravity is weaker-exploration and sampling missions must carefully consider their destination when designing instruments. This holds true for destinations like our Moon (Nash et al 1993) or other planets, where gravity is at least comparable to that of Earth, but also for the extreme case of asteroids, where gravity can be 4-5 orders of magnitude weaker (Hestroffer et al 2019). As examples of the latter microgravity regime, indeed the surfaces of both (101955) Bennu (Barnouin et al 2019) and (162173) Ryugu (Watanabe et al 2019) have been shown to be composed of loosely bound rubble.…”
Section: Introductionmentioning
confidence: 88%
“…E. g., an external acceleration that changes the spin rate by more than 0.17 n the time scale of one orbit would probably be sufficient to drive 2006 HY 51 out of the 964:1 spin-orbit resonance. The distribution of main belt asteroid rotation periods is fairly wide and limited on the high end by approximately 2.4 hours (Hestroffer et al 2019) for radii greater than approximately 0.1 km with most of the objects spinning quite fast. The high rates of rotation are commonly attributed to the secular YORP acceleration, which is caused by irregularities in asteroid's shape, solar irradiation of the surface, and thermal radiation from the surface.…”
Section: Mapping Resonances Of 2006 Hy51mentioning
confidence: 98%
“…Nonetheless, small bodies do not behave like fluids. In effect, being non-monolithic or cohesionless does not mean being fluid, and small bodies are thought to behave more like granular materials that still have certain levels of shear and/or cohesive strengths [175]. By using the limit-analysis approach of plastic theories, Ref.…”
Section: Spin Limitmentioning
confidence: 99%